Hubungan Antara Fatwa dan Hadis - Khairi, Abdul Hasib Fathul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Hadith, as the second principal source of Islamic law after the Qur’an, plays a foundational role in the issuance of fatwas. A fatwa is a legal response given by a mufti to questions posed by the community, requiring strong textual support, particularly from hadith. The relationship between hadith and fatwa is not merely textual, but demands a methodological approach that includes the evaluation of isnad (chain of narration), matn (content), and the socio-historical context of the hadith. A competent mufti must not only cite hadiths, but critically assess their authenticity and relevance to current circumstances. In contemporary times, challenges related to technology, health, and finance compel jurists to engage hadith using analytical and practical methods. Therefore, the connection between hadith and fatwa represents an epistemological interplay between textual authority and juristic reasoning. This study emphasizes the necessity of strengthening hadith methodology as a vital component of responsible and context-sensitive fatwa formulation.